Toplumsal Olaylara Sanal Duyarlılıklar; İnteraktif Sözlükler ve Bedelli Askerlik Hakkı Örneği - (:unkn) unknown (My University, 2016)
Toplum tarafından kutsanan askerlik vazifesinin bedelli hakkı ile muaf hale getirilmesi, toplumda bir hassasiyet oluşturmuş ve tartışma konusu haline gelmiştir. Toplum ve yeni medya teknolojileri ilişkisi göz önüne alındığında zaman zaman yaptığı eylemlerle toplumu peşinden sürükleyen interaktif sözlüklerin (inci sözlük, ekşisözlük, uludağ sözlük, itüsözlük vb.) bedelli askerliğe nasıl yaklaştığı incelenecektir. Bu bağlamda, interaktif sözlüklerin özellikleri ve bu özelliklere bağlı olarak dijital ortamda nasıl örgütlü olarak hareket ettiği ve bu ortak hareketlerin toplumsal sonuçları bedelli askerlik örneği üzerine yazılan entryler ve hazırlanan capsler üzerinden değerlendirilecektir

Being able to exempted from military service by paying Money (paid-for military service) has brought some inconveniences and argumentation in the community especially for the people who consider that the military service is a sanctified phenomenon. As far as the relationship between the community and new media technolgoies are concerned this work will focus on how the interactive dictionaries that has a significant influences on community apporach to the mentioned military service opportunities. In this respect how they take perfectly organized action in the issues and the characteristics of the interactive dictionaries will be evaluated as well as the social consequences for the community. Digital Dictionary, new media, inci sözlük, ekşisözlük, uludağ sözlük, itüsözlük, paid-for military service
Virtual Sensitivity for Social Events; Interactive Dictionaries and Sample of Right to Paid-For Military Service